Prefabulous small houses - Koones, Sheri, 1949- (The Taunton Press, Inc., 2016)
"Prefab home construction has arrived. The benefits of [building] a prefab home (they are better built, use resources more efficiently, and are healthier to live in) apply just as well to vacation homes as they do to primary residences. [This book] explores the beauty, variety, design, and environmentally positive benefits of prefab construction through the wide variety of prefabrication methods in use today and with prefabulous examples from across the country"--Amazon.com.